Evaluation of the efficacy of ultrasound in the diagnosis of cervical lymphadenopathy - Shahad D Ali; Taghreed F Zaidan; Mohammed A Mahdi (College of Dentistry/ University of Baghdad, 2018)
Background: Cervical lymph nodes are prone to involved by a number of pathologic processes. They are common sites for lymphoma, metastasis, and reactive enlargement in a number of conditions. Aims of the study:-Clinical evaluation of patients with cervical lymphadenopathy. Differentiation between benign and malignant lymph nodes by means of ultra sounds (US) and Correlate the US findings with cytological and/or histopathological findings of cervical lymph nodes. Subjects, Materials and Methods:-The present study was carried out over a period of 6 months and included 81 patients of different age groups presenting with cervical lymphadenopathy. Each patient was examined clinically, then comprehensive sonographic examination of the neck for cervical lymph nodes (L.Ns) was performed using ultrasound machine (GE Wipro Proseries). The scanning was performed with the patient in the supine position, and with the neck hyperextended using a pad or pillow under the shoulders in order to provide optimum exposure of the neck. The parameters considered in this study include: site, long axis (L), short axis (S), shape index (S/L), echotexture, margins, ancillary features like calcification, necrosis, matting and surrounding tissue changes. These findings were correlated with fine-needle aspiration cytology, core and excisional biopsy. The nodes were classified as benign (reactive) and malignant (lymphomatous and metastatic). Results: The age of patients ranged from five to seventy five years, they were 45 male and 36 females, there was association between family history and development of malignant lesions. Regarding clinical evaluation, and according to consistency, (13) hard L.Ns were malignant and (1) was benign, (27) rubbery L.Ns were malignant and 40 soft L.Ns were benign. According to fixation to underlying structure, forty one L.Ns were fixed, (40) were malignant and (1) was benign. Forty L. Ns were not fixed, on histopathological evaluation all were benign. On US, the results showed that malignant lymph nodes are mostly appeared as round shape, homogenous echotexture, nodal shape (S/L ratio) accurate for differentiating benign from malignant lymph nodes. Most of the malignant nodes had well-defined borders. Calcifications, necrosis, matting, were characteristically found in benign lymph node. A combined ultrasound-guided and fine-needle aspiration (FNA) diagnosis had a high accuracy as compared with situations in which they were used alone. Conclusions: Sonographic findings have a high accuracy in differentiating benign from malignant cervical lymph nodes. An ultrasound scan can be used as the first-line imaging tool in the diagnostic evaluation of cervical lymphadenopathy. Using gray scale features are particularly useful to identify the causes of cervical lymphadenopathy.